2012
DOI: 10.1007/s13730-012-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous interstitial nephritis in a renal allograft

Abstract: We describe a middle-aged woman in whom granulomatous interstitial nephritis (GIN) developed in a renal allograft. She had undergone bowel resection due to an uncertain diagnosis of active granulomatous bowel disease 30 years earlier. Thereafter, frequent hyperoxaluria as well as calcium oxalate stone and recurrent urinary tract infections had resulted in a progressive deterioration in kidney function over a period of 20 years. She underwent living donor kidney transplantation; however, her kidney function pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Sarcoidosis is a multisystem granulomatous disorder. Various extrarenal lesions have been reported among the cases of sarcoidosis involving the renal allograft, which included lesions in the lung [1,4,5], liver [4], intestine [3], central nervous system [1], lacrimal and parotid glands [6], uvea [5,7,8], and multiple joints [5]. In our case, extrarenal sarcoidosis only involved enlarged mediastinal and bilateral hilar lymph nodes.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Sarcoidosis is a multisystem granulomatous disorder. Various extrarenal lesions have been reported among the cases of sarcoidosis involving the renal allograft, which included lesions in the lung [1,4,5], liver [4], intestine [3], central nervous system [1], lacrimal and parotid glands [6], uvea [5,7,8], and multiple joints [5]. In our case, extrarenal sarcoidosis only involved enlarged mediastinal and bilateral hilar lymph nodes.…”
Section: Discussionmentioning
confidence: 49%
“…Ten cases of sarcoidosis involving a renal allograft have been reported; in seven of these cases, the primary renal disease was sarcoidosis [1,[4][5][6]8]. One case of calcium oxalate stones and recurrent urinary tract infections was reported, and the histological analysis of native kidney tissue revealed granulomas [3]; and the etiology of the primary renal disease was unknown in two cases [2,7]. Although the recurrence rate of sarcoidosis in renal allografts is unclear, it was reported that among the 10 recipients of kidney transplants whose primary renal disease was sarcoidosis, and who were followed for a median period of 52 (range 18-196) months, recurrence of sarcoidosis in their renal allograft was diagnosed in three [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations